Gmelina arborea “death disease” in fast-growth plantations: Effects of soil and climatic conditions on severity and incidence and its implications for wood quality - Marcela Arguedas; María Rodriguez-Solis; Roger Moya; Alexander Berrocal (Forest Systems, 2018)
Aim of study: Plantations are threatened by an emerging disease called “Gmelina death disease”. The objective of this study was measured the incidence and severity of this disease and were correlated with the characteristics of the plantations, micro- and macronutrients in the soil and climatic parameters.